Relación entre la personalidad tipo C y el cáncer : estado del arte (2013)
ABSTRACT: The relationship between type c personality and cancer has been a relevant topic in the last few years and the focusing point for renowned authors in the field of personality and their researches. The different approaches propose: a causal, mediator or nonexistent relationship between these two variables. This relationship is supported by the type c personality construct from three different approaches: like a behavior pattern, a general or an specific coping style in cancer diagnosis. This article compiles the results of an state of the art, wich compile papers that establish a relationship between the type c personality and cancer from 1995 to 2010. Atlas Ti software was used as a methodological tool allowing the development of querys. The conclusions are: 1) the relationship or non relationship between cancer and type c personality is based on the concept of type c personality itself. 2) This concept is constructed depending of the dimensions privileged in each theoretical construct. 3) The relationship between cancer, type c personality and psychosocial factors is also highlighted.